1993
DOI: 10.1128/aem.59.7.2204-2209.1993
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of eight microcystins from thirteen Oscillatoria agardhii strains and structure of a new microcystin

Abstract: Microcystins (cyclic heptapeptide hepatotoxins), isolated from 13 freshwater Oscillatoria agardhii strains from eight different Finnish lakes by high-performance liquid chromatography, were characterized by amino acid analysis, fast atom bombardment mass spectrometry (FABMS), and tandem FABMS (FABMS/collisionaryinduced dissociation/MS). All strains produced two to five different microcystins. In total, eight different compounds, of which five were known microcystins, were isolated. The known compounds identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(28 citation statements)
references
References 42 publications
2
23
0
3
Order By: Relevance
“…Amino acids can then be derivatized with a UV absorbent tag and analyzed by reverse phase LC-UV [83]. Alternatively, they can be derivatized with trifluoroacetic anhydride to make them volatile and then analyzed by gas chromatography [114]. When chiral stationary phases or derivatizing agents are used, it is possible to determine the absolute configuration of the amino acids, which is not possible by MS or NMR alone.…”
Section: Amino Acid Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids can then be derivatized with a UV absorbent tag and analyzed by reverse phase LC-UV [83]. Alternatively, they can be derivatized with trifluoroacetic anhydride to make them volatile and then analyzed by gas chromatography [114]. When chiral stationary phases or derivatizing agents are used, it is possible to determine the absolute configuration of the amino acids, which is not possible by MS or NMR alone.…”
Section: Amino Acid Analysismentioning
confidence: 99%
“…However, Marahiel et al [186] suggested that the concomitant biosynthesis of Dha-and Mdha-containing MC variants could also be the result of the limitation of SAM, the source of the N-methyl group. Such mixtures of MCs containing both Mdha and Dha are common in Planktothrix [114] and Microcystis [139], and partial inactivation of the NMT domain may be a widespread feature of MC biosynthesis.…”
Section: Congeners With Variable Amino Acid At Positionmentioning
confidence: 99%
“…They have been named as such owing to the cyan color of the algae from which they are derived. Hepatotoxic cyclic peptides such as the microcystins57 and nodularins8, 9 are largely responsible for the health risks associated with these algal blooms 10–12. Reports of contaminated water supplies and outbreaks of livestock poisoning have motivated researchers to more closely examine the compounds produced by freshwater blue‐green algae.…”
Section: Introductionmentioning
confidence: 99%
“…Ihr Name leitet sich von der Cyanfarbe der Algen ab, die diese Wasserblüten bilden. Enthaltene hepatotoxische cyclische Peptide wie die Microcystine57 und Nodularine8, 9 sind die Hauptursachen für die gesundheitlichen Risiken beim Umgang mit den Blüten 10–12. Berichte über kontaminierte Wasservorräte und über die Vergiftung von Tierbeständen gaben Anlass, die von Frischwasser‐Blaualgen produzierten Substanzen näher zu untersuchen.…”
Section: Introductionunclassified